A randomized clinical trial of low dose single antibiotic-loaded cement versus high dose dual antibiotic-loaded cement in patients receiving a hip hemiarthroplasty after fracture: A protocol for the WHiTE 8 COPAL study. (1st February 2021) - Agni, Nickil Ramesh; Costa, Matthew L.; Achten, Juul; O'Connor, Heather; Png, May Ee; Peckham, Nicholas; Dutton, Susan J.; Wallis, Stephanie; Milca, Svetlana; Reed, Mike
Abstract : Aims: Patients receiving cemented hemiarthroplasties after hip fracture have a significant risk of deep surgical site infection (SSI). Standard UK practice to minimize the risk of SSI includes the use of antibiotic-loaded bone cement with no consensus regarding type, dose, or antibiotic content of the cement. This is the protocol for a randomized clinical trial to investigate the clinical and cost-effectiveness of high dose dual antibiotic-loaded cement in comparison to low dose single antibiotic-loaded cement in patients 60 years and over receiving a cemented hemiarthroplasty for an intracapsular hip fracture. Methods: The WHiTE 8 Copal Or Palacos Antibiotic Loaded bone cement trial (WHiTE 8 COPAL) is a multicentre, multi-surgeon, parallel, two-arm, randomized clinical trial. The pragmatic study will be embedded in the World Hip Trauma Evaluation (WHiTE) (ISRCTN 63982700). Participants, including those that lack capacity, will be allocated on a 1:1 basis stratified by recruitment centre to either a low dose single antibiotic-loaded bone cement or a high dose dual antibiotic-loaded bone cement. The primary analysis will compare the differences in deep SSI rate as defined by the Centers for Disease Control and Prevention within 90 days of surgery via medical record review and patient self-reported questionnaires. Secondary outcomes include UK Core Outcome Set for hip fractures, complications, rate of antibiotic prescription, resistance patterns of deep SSI, and resource use (more specifically, cost-effectiveness) up to four months post-randomization. A minimum of 4, 920 patients will be recruited to obtain 90% power to detect an absolute difference of 1.5% in the rate of deep SSI at 90 days for the expected 3% deep SSI rate in the control group. Conclusion: The results of this trial will provide evidence regarding clinical and cost-effectiveness between low dose single and high dose dual antibiotic-loaded bone cement, which will inform policy and practice guidelines such as the National Institute for Health and Care Excellence guidance on management of hip fractures. Cite this article: Bone Jt Open  2021;2(2):72–78.